Repurposing HFC-125 to tetrafluoroethylene: A step toward a more sustainable fluoropolymer feedstock strategy - Hiroto Iwasaki; Naoyuki Hoshiya; Yosuke Kishikawa; Jorge Escorihuela; Norio Shibata (iScience)
Summary: The urgency to reduce hydrofluorocarbon (HFC) emissions, particularly HFC-125 (pentafluoroethane, CF3CF2H), has driven efforts to develop sustainable alternatives. Herein, we present a method for converting HFC-125 into tetrafluoroethylene (TFE), an industrially valuable monomer for fluoropolymer production. Our approach uses potassium hexamethyldisilazide (KHMDS), optimizing reaction conditions at −50°C to achieve high TFE yields without any observable byproducts. This low-temperature method offers a safer and more sustainable alternative to traditional high-temperature processes for TFE production, which involve hazardous byproducts and complex handling. We also demonstrated that various chemical reactions using freshly generated TFE, including thiol addition, trifluorovinylation, radical addition, amination, alcohol addition, and polymerization, can be performed, extending the utility of this approach. Moreover, a continuous flow process for the conversion of HFC-125 to TFE at room temperature was achieved without cryogenic equipment. This dual-purpose solution addresses both environmental sustainability of fluorochemicals and the growing demand for fluoropolymers in various industries.